Autograft Reconstruction for Chronic Achilles Tendon Disorders. Issue 3 (September 2017) - Maffulli, Nicola; Aicale, Rocco; Tarantino, Domiziano
Abstract : Surgical management of chronic tendon Achilles ruptures usually requires tendon grafting procedures. Several techniques have been described. We describe the use of 3 different minimally invasive tendon transfer techniques in the management of patients with a chronic rupture of the tendon Achilles, undertaking a free transfer of the semitendinosus tendon, or a transfer of the peroneus brevis or flexor hallucis longus tendons. All 3 techniques produce marked functional improvement, and return to sports is possible in most patients. The advantages of one technique over the others need to be explored. Level of Evidence : Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.